2020
DOI: 10.1096/fj.201902668r
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Gαq/phospholipase Cβ1 signaling pathway returns differentiated cells to a stem‐like state

Abstract: Phospholipase Cβ1 is activated by Gαq to generate calcium signals in response to hormones and neurotransmitters. Besides carrying out this plasma membrane function, PLCβ1 has a cytosolic population that helps to drive the differentiation of PC12 cells by inhibiting a nuclease that promotes RNA‐induced silencing (C3PO). Here, we show that down‐regulating PLCβ1 or reducing its cytosolic population by activating Gαq to localize it to the plasma membrane returns differentiated PC12 and SK‐N‐SH cells to an undiffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…PLCβ1 is associated with loss of proliferation and differentiation 35,36 and these effects are likely to be due to its interaction with C3PO and Ago2, as well as mediating calcium signals. We have previously identified miRs associated PLCβ1 down-regulation in PC12 cells 37 and found . that down-regulating PLCβ1 levels results in substantial reduction in miR101a and miR101b, which may regulate ATP synthase 5B 38 and miR-22 levels by 20%, which regulates Chgb 39 .…”
Section: Discussionmentioning
confidence: 93%
“…PLCβ1 is associated with loss of proliferation and differentiation 35,36 and these effects are likely to be due to its interaction with C3PO and Ago2, as well as mediating calcium signals. We have previously identified miRs associated PLCβ1 down-regulation in PC12 cells 37 and found . that down-regulating PLCβ1 levels results in substantial reduction in miR101a and miR101b, which may regulate ATP synthase 5B 38 and miR-22 levels by 20%, which regulates Chgb 39 .…”
Section: Discussionmentioning
confidence: 93%
“…PLCβ1 is associated with loss of proliferation and differentiation [38,39] and these effects are likely to be due to its interaction with C3PO and Ago2, as well as mediating calcium signals. We have previously identi ed miRs associated PLCβ1 down-regulation in PC12 cells [40] and found that down-regulating PLCβ1 levels results in substantial reduction in miR101a and miR101b, which may regulate ATP synthase 5B [41]and miR-22 levels by 20%, which regulates Chgb [42]. The loss of these miRs, along with the observation that loss of cytosolic PLCβ1 or sustained neurotransmitter activation of Gαq returns PC12 cells to the undifferentiated state, may indicate that the increased number of stress granules may sequester mRNAs important for de ning cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting: We used an establish procedure [40] with modi cations. Samples were grown in 100 mm dishes plates and were treated with MG132 at a nal concentration of 250 nM 24 hours before collection.…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular factors such as Ang II, epinephrine, histamine and bradykinin can bind to corresponding receptors to activate PLC-β1 protein, further promote CaM expression and conformational changes in cells, thus regulating intracellular Ca 2+ concentration and calcium kinase activity, producing a series of biological effects (Fig. 2 ) [ 17 ]. Recent studies have found that the contents of PLC-β1 and CaM in HCC, colon cancer and breast cancer tissues are significantly increased, which can promote the growth, invasion and movement of tumor cells [ 18 – 20 ].…”
Section: Introductionmentioning
confidence: 99%